Clinical outcomes after fast-track care in women undergoing laparoscopic hysterectomy. Issue 3 (December 2015) - Minig, Lucas; Chuang, Linus; Patrono, Maria Guadalupe; Fernandez-Chereguini, María; Cárdenas-Rebollo, Jose M.; Biffi, Roberto
Abstract: Objective: To evaluate the feasibility and safety of multimodal perioperative care after laparoscopic hysterectomy. Methods: A prospective observational study was performed at Clara Campal Comprehensive Cancer Center, Madrid, Spain, between April 1, 2011, and July 30, 2014, and included women who were scheduled to undergo a laparoscopic hysterectomy. Fast-track (multimodal) care included provision of full preoperative verbal and written information, intravenous dexamethasone (8 mg) during surgery, removal of the urinary catheter at the end of surgery, and early mobilization and solid food intake. The main outcome was the length of hospital stay. Results: Overall, 88 patients were included. The median hospital stay was 22.7 hours (range 5–72). Same-day discharge was feasible in 24 (27%) patients. A total of 51 (58%) women were discharged after overnight stay, 46 (90%) of whom elected to do so because of personal preference. Finally, 13 (15%) patients were discharged at least 36 hours after surgery. Eleven (13%) women visited the emergency unit after discharge and 3 (3%) were readmitted. Conclusion: The perioperative multimodal recovery program is safe and feasible in a selected group of women after an elective laparoscopic hysterectomy.